2019
DOI: 10.7861/clinmedicine.19-4-282
|View full text |Cite
|
Sign up to set email alerts
|

Surveying, shoring, strengthening: rebuilding medical morale from its foundations

Abstract: Significant uncertainty surrounds the sustainability of healthcare services in which junior doctors work. It is essential that student and foundation doctors (SFDs) are actively engaged if workforce morale is rebuilt. This narrative review explores the evidence driving the individual work-streams of the Royal College of Physicians' newly formed Student and Foundation Doctor Network. Undergraduate and postgraduate training reform has coincided with concerning feedback from newly qualified doctors. System-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This review supported existing evidence that the junior doctor's first year is pervasive with unrealistic expectations of resilience. 12,19 Progressive amounts of fatigue and anger were demonstrated as the year continues, 19 with poor work-life balance leading to disillusionment, and a 50% attrition rate in their second year. 44 However, it also revealed that the mentoring relationship permits vulnerability and emotionality, 44 which may facilitate the creation of first-year doctors with greater overall well-being, who are less susceptible to burn-out, and better supported through the otherwise silenced psychosocial, professional and cultural demands of their transition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This review supported existing evidence that the junior doctor's first year is pervasive with unrealistic expectations of resilience. 12,19 Progressive amounts of fatigue and anger were demonstrated as the year continues, 19 with poor work-life balance leading to disillusionment, and a 50% attrition rate in their second year. 44 However, it also revealed that the mentoring relationship permits vulnerability and emotionality, 44 which may facilitate the creation of first-year doctors with greater overall well-being, who are less susceptible to burn-out, and better supported through the otherwise silenced psychosocial, professional and cultural demands of their transition.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 In contrast, mentoring, aims for individualised outcomes, long-term transformational development, 6 conscious and dynamic interest in the mentee's success 9 and a fostering of trust that provides guidance through their personal and professional development. 1 To the knowledge of the authors, although the benefits of mentorship in broader medical cohorts are already known, no systematic reviews exist that synthesise articles on mentorship for first-year doctors specifically, despite the unique transition difficulties and vulnerability identified within this group; the shift from medical student to first-year doctor is widely described as notoriously challenging, 3,[10][11][12][13][14] with graduates and supervisors in one study reporting a failure rate of 28.3%. 12 Transition failure, or transition shock, 10,15 is attributed to performance gaps between academia and clinical practice, which manifest in relation to increasing complexity of communication, responsibility, time management, ability to cope with emergencies and capacity to manage overall resilience and professionalism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations